Dignity at the Workplace: Evolution of the Construct and Development of Workplace Dignity Scale - Tiwari, Anjali; Sharma, Radha R. (Frontiers in Psychology, 2019)
Concerns about workplace dignity (WPD) have long driven researchers and practitioners to explore ways of measuring it. It is essential for organizations to understand, how employees perceive the workplace dignity for positive employee outcomes. The paper reviews literature, traces the development of WPD and finds the gap. The purpose of this paper is to evolve and operationalize the construct of ‘workplace dignity’, and develop and standardize a measure for it which will pave the way for future studies to empirically test the role of workplace dignity on organizational outcomes such as employee engagement and retention and the like. This is perhaps the maiden attempt for conceptualization and operationalization of the construct of workplace dignity, thus it contributes to the extant knowledge and has implications for academics and practitioners.